ACUPUNCTURE ANESTHESIA ON AWAKE CRANIOTOMY FOR TUMOR REMOVAL: A CASE REPORT - Arief Kurniawan; Nur Pudyastuti Pratiwi (Journal of Innovation Research and Knowledge, 2022)
Acupuncture anesthesia is a type of acupuncture-based anesthesia. Anesthesia is achieved by placing needles into certain spots on the body, and the surgery is carried out while the patient is fully aware that he or she is no longer in pain. This approach avoids anesthesia-induced physiological dysfunction and post-operative anesthetic side effects. Acupuncture anesthesia is being used for head, chest, abdominal surgery, and awake craniotomy in persons of all ages. The anesthesiologist's job in awake craniotomy is to deliver appropriate sedation and analgesia in patients who are still conscious and cooperative during the surgery while maintaining breathing and hemodynamic stability. A 42-year-old man was diagnosed with an oligodendroglioma-like supratentorial tumor. He was referred for three weeks of vomiting and headaches. His ECG and thoracic pictures were normal in the lab, but his MSCT revealed a hypodense lesion in the left temporal with modest mass effects. On an awake craniotomy, tumor resection was performed under acupuncture anesthesia. Electroacupuncture induction takes 20 minutes with the use of supplementary medications such as midazolam, fentanyl, and lidocaine. On a compliant and comfortable patient, the surgery can be completed without difficulty. After being examined in the PACU for 30 minutes without discomfort or PONV, he was transferred to the ward. We came to the conclusion that our patient responded well to the acupuncture anesthetic treatment.